Effect of ZnO Nanoparticles on AST Activity in Gingival Cervicular Fluid of smokers and Nonsmokers Chronic Periodontitis Patients: in Vitro Study - Zainab A. Salman (Journal of Global Pharma Technology, 2018)
Objectives: current studies to estimate the effects of cigarette smoking on oral periodontal health, and due to the lack of studies that simultaneously compared the periodontal condition smokers with periodontal disorders, and nonsmokers with periodontal disorders, we assessed the periodontal condition in these two groups. The effect of ZnO NPs on aspartate aminotransferase (AST) activity in Gingival Cervicular Fluid (GCF) of smokers and nonsmokers patients with chronic periodontitis was studied as a part of assessment of tissue damage that has been occur due periodontal disease and smoking. Nanoparticles (NPs) have been studied in different areas to evaluate the effect of nanoparticles on the activity of enzyme as a part of more accurate diagnosis. Materials and Methods: GCF samples for 26 persons (aged 35-50 years) with chronic periodontitis were collected as patients group. Powder of ZnO NPs (< 80 nm) was used in this study. The activities of AST enzyme in GCF were estimated in (smoker and nonsmoker) patients group with and without ZnO NPs as a pertinent biomarker of chronic periodontitis. The impact of ZnO NPs on AST activity in GCF of patients with chronic periodontitis was evaluated in terms of group with AST activity was assessed by colorimetric method. Results: results were showed that AST activity in smoker patients group with and without ZnO NPs was higher than its activity in nonsmoker patients. Conclusion: The impact of ZnO NPs on AST efficiency in GCF may be due to the vital role of ZnO NPs in durability against pathogens, in another hand, this impact may be reflects the changes on protein structure after interaction with ZnO NPs.Keywords: Gingival crevicular Fluid, aspartate aminotransferase , ZnO NPs , smoker and nonsmoker Chronic periodontitis .